2004
DOI: 10.1158/0008-5472.can-03-3214
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of High-Level Chromosomal Instability Is Associated with Integration of Human Papillomavirus Type 16 in Cervical Keratinocytes

Abstract: Whereas two key steps in cervical carcinogenesis are integration of high-risk human papillomavirus (HR-HPV) and acquisition of an unstable host genome, the temporal association between these events is poorly understood. Chromosomal instability is induced when HR-HPV E7 oncoprotein is overexpressed from heterologous promoters in vitro. However, it is not known whether such events occur at the "physiologically" elevated levels of E7 produced by deregulation of the homologous HR-HPV promoter after integration. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
164
0
10

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 180 publications
(179 citation statements)
references
References 43 publications
5
164
0
10
Order By: Relevance
“…It has recently been found that the clinical outcome of preinvasive cervical lesions can be accurately predicted by the physical status of the hrHPV genome (integrated vs episomal) in conjunction with viral load (Wanram et al, 2009). The transition from low-grade dysplastic lesion harbouring episomal genomes to late-stage invasive carcinoma containing only integrated copies has been shown to occur by an intermediate step in which episomal and integrated genomes co-exist (Pett et al, 2004). Cells harbouring both genome types were characterised by copy number imbalances that predominantly comprised whole chromosome gains or losses, similar to the genetic events observed in vulval neoplasia in this study.…”
Section: Vulval and Cxscc May Be Associated With Different Genetic Alsupporting
confidence: 75%
“…It has recently been found that the clinical outcome of preinvasive cervical lesions can be accurately predicted by the physical status of the hrHPV genome (integrated vs episomal) in conjunction with viral load (Wanram et al, 2009). The transition from low-grade dysplastic lesion harbouring episomal genomes to late-stage invasive carcinoma containing only integrated copies has been shown to occur by an intermediate step in which episomal and integrated genomes co-exist (Pett et al, 2004). Cells harbouring both genome types were characterised by copy number imbalances that predominantly comprised whole chromosome gains or losses, similar to the genetic events observed in vulval neoplasia in this study.…”
Section: Vulval and Cxscc May Be Associated With Different Genetic Alsupporting
confidence: 75%
“…It is still a matter of debate whether HPV DNA integration precedes E6/E7 induced genetic instability or rather is a consequence thereof. In an in vitro study acquisition of high levels of genomic instability in cervical keratinocytes in monolayer culture occurred after integration of HPV16 (Pett et al, 2004). On the other hand, Melsheimer et al (2004) have shown that in CIN and cervical carcinomas aneuploidization precedes integration of HPV DNA in the progression of cervical dysplasia.…”
Section: Figurementioning
confidence: 99%
“…HPV integration in W12 cells was associated with an increase in levels of detectable E7 protein. Maximal E7 levels correlated with the acquisition of structural chromosomal abnormalities (Alazawi et al, 2002;Pett et al, 2004). High oncogene levels are attributed to the functional loss of the viral E2 gene product which acts as an intrinsic repressor of E6/E7 expression (Romanczuk and Howley, 1992).…”
Section: Figurementioning
confidence: 99%
“…Thus, HRHPV integration and disruption͞deletion of E2 leads to increased expression of the viral oncogenes (7,8). Cells containing integrated HRHPV acquire a growth advantage over cells harboring episomal HRHPV (the natural viral state in productive infections) and show increased genomic instability (9)(10)(11).…”
mentioning
confidence: 99%
“…We have tested our hypothesis by using the unique HPV16-containing cervical keratinocyte cell line W12 in monolayer culture (12); this represents a useful system to investigate the effects of HPV16 infection in basal cervical squamous cells, the key site of deregulation of HRHPV viral oncogenes in cervical neoplasia (10). W12 was derived from a low-grade squamous intraepithelial lesion (LG-SIL), which resulted from ''natural'' infection in vivo with HPV16, the HRHPV type most commonly detected in cervical carcinomas (15).…”
mentioning
confidence: 99%